TRANSFORMASI SALURAN POLITIK ETNIS TIONGHOA DI PROVINSI SUMATERA UTARA PASCA ORDE BARU - Rudi Salam Sinaga (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2022)
General elections (elections) that took place in the post-new order era (1999-2014) with various changes to the electoral system and the results of the elections have presented a different geopolitical situation than before. This condition resulted in a "new" geopolitics at every level of the election, including in North Sumatra Province. This paper aims to explore the transformation of ethnic Chinese political channels in North Sumatra province in the 4 post-New Order elections in the context of the election of members of the regional parliament for North Sumatra province. This paper uses a qualitative descriptive method. Data obtained through interviews, literature and documentation. The interview informants came from several ethnic Chinese politicians, several political party officials and ethnic Chinese community leaders in North Sumatra. The results of this paper get a transformation of changes in ethnic Chinese political channels as a response to the strengthening of democratic values and opportunities to gain political office are increasingly wide open.